Oxford textbook of advanced critical care echocardiography - McLean, Anthony; Huang, Stephen (Stephen J.); Hilton, Andrew (Oxford : Oxford University Press, 2020)
Provides a physiological and evidence-based reference guide to the principles and techniques of advanced echocardiography. Both transoesophageal and transthoracic echocardiography are addressed making this an ideal adjunct to more advanced echo courses for intensivists.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 26, 2020).
Keywords: Echocardiography; Critical care medicine